Method of discrete approximations of gravity field on delineation of promising sections - Arsanukayev, Z.Z. (Geofizicheskiy Zhurnal, 2014)
The theme considered in the article is connected with the numerical solution of Laplas equation while solving the problem of gravimetry. It is shown, that the use of a method of discrete approximations reduces a problem of restoration of values of a gravitational field on set to drawing up and the solving of systems of the linear algebraic equations (LAE). With applying the software package developed by the author, numerical calculation with solving of LAE of the big usages is carried out during the problem solution to delineate a promising section.